P097 Incidence of abnormal dreams and nightmares with lemborexant in adults with insomnia: results from two Phase 3 studies. (7th October 2021) - Roth, T; Yardley, J; Pinner, K; Kumar, D; Cheng, J; Moline, M
Abstract: Introduction: Abnormal dreams and nightmares have been reported by insomnia patients before and after treatment with sedative-hypnotics. Since dual-orexin-receptor-antagonists such as lemborexant (LEM; approved in multiple countries for adult insomnia) increase REM sleep, during which dream content is more likely to be recalled, we assessed the frequency of nightmares/abnormal dreams in Phase 3 studies. Methods: Study 303 (SUNRISE-2) was a 12mo, randomized, double-blind, placebo (PBO)-controlled (first 6mo [Period 1]), phase 3 study that enrolled subjects ≥18y with insomnia disorder and ISI scores ≥15. During Period 1, the safety analysis set (SAS) included: PBO, n=319; LEM 5mg, (LEM5), n=314; LEM 10mg (LEM10), n=314. Study 304 (SUNRISE-1) was a 1mo, randomized, double-blind, PBO- and active-controlled (zolpidem tartrate extended-release 6.25mg [ZOL-ER]) study of LEM5 and LEM10. The SAS included: PBO, n=209; ZOL-ER, n=263; LEM5, n=266; LEM10, n=268. Results: In Study 303, Period 1, 28/947 subjects (3.0%) reported nightmares (n=12; PBO-1; LEM5-4; LEM10-7) or abnormal dreams (n=17; PBO-6; LEM5-7; LEM10-4) as treatment-emergent adverse events (TEAEs). In Study 304, 12/1006 subjects (1.2%) reported nightmares (n=4; PBO-1; ZOL-ER-0; LEM5-2; LEM10-1) or abnormal dreams (n=8; PBO-1; ZOL-ER-3; LEM5-0; LEM10-4). 32/40 subjects (80.0%) reporting these events were female (% females in the studies: 303=67.9%; 304=86.4%). In the LEM groups, 11/28 subjects (39.3%) reported the TEAE within 3 days of treatment initiation. There were 2 TEAEs of nightmare/abnormal dreams during the PBO run-in prior to randomization. Conclusion: Abnormal dreams/nightmares were not common events in either study. Incidence was slightly higher with LEM10 and proportional to enrollment based on sex.